PROFESIONALISME GURU PAUD MELATI TERPADU DALAM MENINGKATKAN MUTU PENDIDIKAN PADA ERA REVOLUSI INDUSTRI 4.0 - Sapriani, Rizki (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Teacher professionalism refers to abilities in pedagogical, personal, social and professional competencies. Teacher professionalism is now increasingly challenged in improving the quality of education in Indonesia, which is still inferior to neighboring countries. The era of industrial revolution 4.0 makes teachers have to prepare themselves to face this challenge, education and learning are demanded to change. This study is about professional teachers in PAUD Melati Terpadu in education in the industrial revolution era 4.0 which aims to determine teacher professional competence in the future. This study uses qualitative methods with field research. Data is taken by making observations directly to the object of research. The results of this study are descriptions of the implementation of PAUD Melati Terpadu learning by teachers to improve the quality of early childhood education.